RANCANG BANGUN SISTEM E-LEARNING FLATDESIGN UNTUK PEMULA DENGAN DATA JSON DAN METODE RAD - Dhian Sweetania; Nani Mintarsih; MS. Herawati (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2022)
Flat design is a design style that is popular today. One of the reasons for the popularity of flat design is its simple appearance. Even though it has a simple appearance, flat design can convey a message effectively to anyone who sees it. Flat design is now easily found, such as on Android displays, websites, and so on. The popularity of flat design has an impact on designers, especially novice designers, to learn it. Studying flat design can be done self-taught, such as looking for sources that discuss flat design. Finding these sources can take a lot of time, due to the large number of available sources. Therefore the Flatin website is here to overcome this. The Flatin website has a learning suite with various features, such as modules and quizzes. In addition to the learning series, the Flatin website provides e-certificates and learning videos to users who have completed the learning series. This website was created using the programming language JavaScript, PHP, SQL and MySQL database. The method used in this research is Rapid Application Development (RAD). REST architecture, which is basically operated over HTTP (Hypertext Transfer Protocol), which refers to the process of reading a particular web page containing a JSON file. This file describes and contains the content to be presented to the user. After going through a certain definition process, the user will be able to access the available application interfaces. When testing produces appropriate results, the website can be widely accessed. Website access can be accessed through https://www.flatin.my.id/.